P1-S6.14 Interventions to increase re-testing for repeat chlamydial infection: a systematic review and meta-analysis. (10th July 2011) - Ali, H; Guy, R; Low, N; Bauer, H; Walker, J; Klausner, J; Donovan, B; Kaldor, J; Hocking, J
Abstract : Background: Repeat infection with Chlamydia trachomatis following treatment is common and increases the risk of sequelae. Despite clinical guidelines recommending re-testing within 3 months of treatment, re-testing rates remains low. We undertook a systematic review of studies which evaluated interventions aimed at increasing re-testing for repeat chlamydial infection. Methods: We searched Medline, EMBASE, trial registries, and conference websites from 2000 to September 2010 using variations of the terms "chlamydia" and "re-testing" and "intervention" to identify studies which compared rates of re-testing for repeat chlamydial infection between patients receiving and not receiving an intervention. We used meta-analysis methods to calculate the overall RR effect on re-testing rates, as well as undertaking a sub-analysis by strategy type. Results: We identified eight studies satisfying the inclusion criteria, including four randomised controlled trials and four controlled observational studies. The studies described 12 intervention strategies. All were conducted in the USA. The overall effect estimate RR for any strategy was 1.45 (95% CI 1.35 to 1.55); RR=1.80 (95% CI 1.63 to 1.97) for four studies using reminders such as postcards, phone calls, letters and emails (individually or in combination); 1.25 (95% CI 1.12 to 1.38) for four studies using mailed screening kits with or without reminders; 2.15 (95% CI 0.92 to 3.37) for two studies using motivational interviewing with or without reminders; 1.35 (95% CI 0.88 to 1.82) for one study promoting re-testing guidelines to clinicians; and 1.16 (95% CI 0.38 to 1.93) for one study using a 20 patient incentive to encourage re-testing. Conclusion: Reminders and mailed screening kits can increase re-testing rates by 80% and 25% respectively.